Analisis perbandingan aktivitas antioksidan virgin coconut oil dan extra virgin olive oil terhadap kadar malondialdehid pada tikus putih obesitas hiperglikemik - Churiani; Aryanti R. Bamahry; Namirah, Hanna Aulia; Safitri, Asrini; Lantara, A. Millaty Halifah Dirgahayu (UHAMKA PRESS, 2024)
Obesity is specification by extreme accumulation of body fat, which can make to oxidative stress due to an disproportion among free radicals and antioxidants. Conditions associated with obesity, such as hyperglycemia, are significant markers for diabetes mellitus. The increase prevalence of obesity and diabetes in Indonesia underscores the need for effective management strategies such as administering compounds that have antioxidant properties to protect body cells against oxidative damage. This study aims to compare the effectiveness of Virgin Coconut Oil (VCO) and Extra Virgin Olive Oil (EVOO) in reducing malondialdehyde (MDA) levels in hyperglycemic obese white mice. Both VCO and EVOO contain antioxidants, including phenolics and α-tocopherol. Notably, EVOO is rich in hydroxytyrosol, a potent antioxidant compound, and has a total phenolic content ranging from 42.35 to 190.98 mg GAE (gallic acid equivalent), while VCO contains only 1.16 to 12.54 mg GAE. This true experimental study involved three groups of hyperglycemic obese rats: a negative control, VCO, and EVOO, with interventions lasting 14 days. MDA levels were measured on days 0, 7, and 14. Results indicated that both oils effectively reduced MDA levels, with EVOO demonstrating a more significant reduction of 0.43 μmol/l compared to VCO's reduction of 0.16 μmol/l, highlighting EVOO's superior efficacy to reduced oxidative stress.